Penguatan Sikap Moderasi Beragama Pada Siswa SD Fransiskus Bukittinggi - Fadila, Rahmi; Aprison, Wedra (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research is motivated by the social interaction challenges faced by students at SD Fransiskus Bukittinggi, who come from various religious backgrounds, including Islam, Christianity, Catholicism, Hinduism, and Buddhism. Although this diversity could enrich the learning experience, religious differences often led to difficulties in forming social relationships among students, creating social distance, misunderstandings, and the emergence of stereotypes. These issues had the potential to create conflicts and tensions within the school environment. The research aims to describe efforts to strengthen religious moderation, as well as the supporting and inhibiting factors, in order to promote harmony amidst diversity. A qualitative descriptive approach was used, employing observation, interviews, and documentation methods. The school principal and religious teachers served as the primary data sources, while students were considered supporting informants. The results show that efforts to strengthen religious moderation are carried out through the insertion of moderation values in religious education, interactive classroom discussions, extracurricular activities that encourage interfaith cooperation, and the evaluation of students’ attitudes. Supporting factors include school policies, strong cohesion between teachers and students, and adequate facilities. However, obstacles faced include the influence of social media, which can reinforcenegative stereotypes and hinder positive interactions between students.